Cognitive impairment in cerebral toxoplasmosis with pre-HAART HIV infection: a case report - Dico Gunawijaya; Dian Kusumastuti; Widya Putra; Nurlina Ekasari (Intisari Sains Medis, 2019)
Background: Dementia can be caused by infection in the central nervous system, primarily by HIV infection. The majority of the symptoms are short-term memory impairment accompanied by concentration and motoric deceleration. Opportunistic infections of Toxoplasma gondii often accompanies and aggravates the cognitive impairment that occurs.Case: Male, 55-year-old, complained by the family to be forgetful and hard to concentrate since last two weeks and got worse over time. The daily activities of the patient were often disturbed. The awareness, cranial nerve, motor function, sensory, and autonomic were within normal limits. Laboratory tests showed reactive IgG anti-toxoplasma (4520.00 IU / mL) and CD4 128 cells/ÂµL. A non-contrast head CT-Scan showed multiple ill-bordered hypodense lesions with broad peripheral edema in left cerebral hemispheres. Test of cognitive function with MoCA-Ina scored 13 and MMSE scored 19.Discussion: Dementia in HIV manifests as a collection of symptoms of cognitive and motor impairment that interfere with daily activities. The pathogenesis is thought to be caused by interactions with viral proteins and secondary inflammation. Chronic toxoplasmosis is associated with the incidence of dementia in HIV, which usually occurs when CD4 <200 cells/ÂµL. The underlying pathology of inflammation responsible for neurotransmitter modulation and oxidative stress. HAART administration related to a risk reduction of dementia in HIV. High penetrating antiretroviral lowers viral load better, so it can reliably reduce inflammation while slowing the progression of cognitive impairment.Conclusion: HIV infection often leads to dementia, either with or without opportunistic infections. Currently, HAART is the only therapy, accompanied by education and follow-up of the patient's cognitive function.